KERJA SAMA OPERASI PENYEDIAAN LISTRIK DI INDONESIA BAGIAN TIMUR: HARAPAN DAN HAMBATAN - Malvin Jati Kuncara Alam; Rayhan Fiqi Fansuri (Fakultas Hukum Universitas Borobudur, 2022)
Electric power is one of the vital resources where its use not only affects human life but is also strategic in carrying out national development goals. In this regard, electric power currently plays a major role in realizing Indonesia's vision to achieve net zero emissions. However, even though several regulations have been issued to encourage this effort, it seems that the rate of development of renewable electricity is always off target or slow. In the midst of this progress, one of the ways to accelerate the supply of electricity with new renewable energy is through Joint Operations. However, it seems that this scheme is also experiencing problems from a regulatory perspective. Therefore, this paper will identify the problems in Joint Operations and Provision of electricity in general with the formulation of the problem how Joint Operations can optimize the Electrification Ratio in eastern Indonesia? and what are the obstacles in the implementation of the Operational Cooperation for the Supply of Electricity in Eastern Indonesia? The type of research used by the author is normative juridical, with statutory, case and conceptual approaches as well as literature study data collection techniques. After conducting research, it can be seen that basically Operational Cooperation can solve problems that exist in the practice of electricity supply but are hampered by regulations including regarding the concept of Cooperation itself, Single Buyer, and excess power.